Factors affecting performance and productivity of nurses: professional attitude, organisational justice, organisational culture and mobbing. (29th March 2016) - Terzioglu, Fusun; Temel, Safiye; Uslu Sahan, Fatma
Abstract : Aim: To identify relationships among variables affecting nurses' performance and productivity, namely professional attitudes, organisational culture, organisational justice and exposure to mobbing. Background: The determination of the factors affecting performance and productivity is important for providing efficient nursing services. These factors have been investigated in the literature independently, but the relationship among them has not been clearly identified. Methods: This cross‐sectional questionnaire study included 772 nurses working in a University Hospital accredited by Joint Commission International. Results: The professional attitude score of the nurses was high (4.35 ± 0.63). However, their organisational justice (2.22 ± 1.26) and organisational culture (2.47 ± 0.71) scores were low. Nurses were subjected to mobbing at a high level (0.82 ± 0.78). As the organisational justice increased, the organisational culture increased and the mobbing decreased. As the organisation culture decreased, the mobbing increased. Conclusions: There was a positive correlation between organisation culture and organisational justice of the nurses and a negative correlation with mobbing. Implications for nursing management: The results of the study are essential for improving nurses' performance and productivity.